Increasing Quality of Reciting Al-Qur’an by Using Ummi Method: Community Assistance & Empowering Al-Ihsan Mosque for Dhuafa - Cahyono, Agus Eko; Herawati, Yayuk Widyastuti; Al Anshory, Abdul Muntaqim (International Journal of Social Science and Community Service, 2025)
This study examines the implementation of the Ummi method in learning Al-Qur’an at Al-Ihsan Mosque, Malang, and its role in community empowerment. The Ummi method, known for its structured and systematic approach, enhances reading accuracy and comprehension of Tajwid among the congregation. The findings reveal that the application of this method has significantly improved participants' Quranic reading skills through direct instruction, repetition, and affectionate teaching. Furthermore, Al-Ihsan Mosque has played a vital role in empowering the underprivileged through the effective management of infaq funds, scholarship programs, and basic needs assistance. However, challenges such as limited teaching space and the need for professional human resource management hinder the effectiveness of these initiatives. To optimize the impact, it is recommended to increase learning facilities, strengthen community collaborations, and establish objective assessment tools for aid distribution. Strengthening youth involvement and professional fund management will further enhance the sustainability of these programs, ensuring that community empowerment efforts are both impactful and equitable.